Endoscopic ultrasound-guided thrombin injection, a management approach for visceral artery pseudoaneurysms - Maharshi, Sudhir; Sharma, Shyam Sunder; Sharma, Deepak; Sapra, Bharat; Nijhawan, Sandeep (Endoscopy International Open, 2020)
Background and study aims Pseudoaneurysms are usually associated with high rates of morbidity and mortality. There are limited data in the literature on endoscopic ultrasound (EUS)-guided thrombin injection for pseudoaneurysms. The aim of this study is to assess the efficacy and safety of EUS-guided thrombin injection for pseudoaneurysms.Patients and methods This prospective study was conducted in our department between January and December 2018. All patients with symptomatic visceral artery pseudoaneurysms, who were unable to undergo angioembolization, were enrolled consecutively. Data related to demography, laboratory parameters, radiological imaging, pseudoaneurysms, and endotherapy were analyzed.Results Eight patients with median age 34 years (27–58 years), all men, were studied. The vessel involved was the splenic artery in 5 patients (62.5 %), the left hepatic artery in 2 (25 %), and the gastroduodenal artery in 1 patient (12.5%). The median size of the pseudoaneurysms was 2.9 cm × 2.6 cm (range, 1.8 × 1.9–4 × 5 cm). The median thrombin requirement was 400 IU (range, 200–500 IU) for loss of Doppler flow signals. EUS after 3 months showed obliterated pseudoaneurysms in 7 patients (87.5 %), while recurrence was observed in 1 patient (12.5 %) after 6 weeks.Conclusions EUS-guided thrombin injection may be a new option for the management of pseudoaneurysms.